The impact of domestic debt on inflation rate: Empirical evidence from Nigeria - samuel, olufemi; Olugbamiye, Olorunleke Dominic (Journal of Indonesian Applied Economics, 2024)
Using annual time series data this study examines the relationship between Nigeria's domestic debt and the country's inflation rate between 1981 and 2022 using ARDL estimation technique. The study employed Augment Dickey Fuller unit root test to determine the stationarity of each variable and the result revealed that inflation and GDP growth rates were stationary at integration level I(0), whereas all other variables were integrated at I(1). The bound test revealed that there is a long run relationship between the variables which implies that all the variable cointegrate. The study revealed that that domestic debt and interest rate had negative impact on inflation rate while external debt, economic growth and money supply had positive impact on inflation rate. Since the study found that domestic debt helps to reduce inflation, therefore government should often consider borrow from within the country as it reduces inflation as against external borrowings that increases inflation